A simple video-based timing system for on-ice team testing in ice hockey: a technical report - Larson, D. P.; Noonan, B. C. (The Journal of Strength and Conditioning Research, 2014)
The purpose of this study was to describe and evaluate a newly developed on-ice timing system for team evaluation in the sport of ice hockey. We hypothesized that this new, simple, inexpensive, timing system would prove to be highly accurate and reliable. Six adult subjects (age 30.4 ± 6.2 years) performed on ice tests of acceleration and conditioning. The performance times of the subjects were recorded using a handheld stopwatch, photocell, and high-speed (240 frames per second) video. These results were then compared to allow for accuracy calculations of the stopwatch and video as compared with filtered photocell timing that was used as the "gold standard." Accuracy was evaluated using maximal differences, typical error/coefficient of variation (CV), and intraclass correlation coefficients (ICCs) between the timing methods. The reliability of the video method was evaluated using the same variables in a test-retest analysis both within and between evaluators. The video timing method proved to be both highly accurate (ICC: 0.96-0.99 and CV: 0.1-0.6% as compared with the photocell method) and reliable (ICC and CV within and between evaluators: 0.99 and 0.08%, respectively). This video-based timing method provides a very rapid means of collecting a high volume of very accurate and reliable on-ice measures of skating speed and conditioning, and can easily be adapted to other testing surfaces and parameters.